The Future Of Decentralization Politics In Indonesia - Ahmad Sholikin (Universitas Islam Darul Ulum Lamongan, 2018)
Without much preparation, Indonesia in 2000 the new system replaced the previous centralized governance system and development planning with various decentralization programs. The reforms gave greater authority, political power, and financial resources directly to districts and cities, through the provinces. Strengths transferred include those who carry out various responsibilities in the fields of health, primary and secondary education, public works, environment, communication, transportation, agriculture, manufacturing, and other economic sectors. At the same time, the government replaced the cash-based public finance system, a single-entry financial system with a modern double-entry accounting system that uses one treasury account; based on performance; and has transparent public cash management, strict expenditure and financial controls with performance indicators, computerized reporting, and a tightly scheduled audit system.